Choice not chance : rules for building a fierce competitor - McCallie, Joanne P., 1965- (Hoboken, N.J. : Wiley, 2012)
'Foreword by Mike Krzyzewski, Duke's Men Basketball CoachA celebrated coach reveals the secrets to building a fierce competitorAt age 26, Joanne P. McCallie, a.k.a. Coach P, began her career at Maine, where in the span of eight years, she elevated the women's basketball program to a very competitive team that outdrew the men's crowds, a rarity in college sports. Over her tenure, she created the Choice Not Chance (CNC) philosophy, training kids how to think and focus on making the correct choices in life. She imparted her passionate philosophy to all of her players and now brings it to her efforts as head coach at Duke. Choice Not Chancehighlights McCallie's lessons for building a fierce competitor, such as'Going against the grain,''Never become satisfied,' and'Enjoy the prospect of getting better daily.'The CNC philosophy is widely used by McCallie, her staff, and players, who are very active in the community speaking about'CNC.' Joanne P. McCallie is head coach of the Duke Women's Basketball team and was the ACC Coach of the Year in 2010 McCallie became the first coach in Division I history to be crowned champion in four different conferences, as well as the first coach in NCAA history to garner coach of the year accolades in four different leagues A native of Brunswick, Maine, McCallie owns a career mark of 431-174 and is entering her 20th year as a head coach at Maine, Michigan State and Duke; as a coach and player, she has led her teams to 15 conference titles, 19 NCAA Tournament appearances, seven NCAA Sweet 16 appearances, five NCAA Elite Eight appearances, three NCAA Final Four appearances and three NCAA Championship game appearances During the 2004-05 season at Michigan State, she won the Big Ten Regular Season and Tournament Championship en route to a National Championship game appearance. For her efforts she was named the Associated Press National Coach of the Year McCallie has taught her teams to play with passion and fight hard for recognition, and her teams have achieved remarkable success. Apply her wisdom to your teams, your employees, and your own life'--
Keywords: McCallie, Joanne P., -- 1965-; Coaches (Athletics) -- United States -- Biography; Women coaches (Athletics) -- United States -- Biography; Coaching (Athletics) -- United States; Competition -- United States